English Dipthong Found in Song Titled Blue Jeans by Gangga Kusuma - Devi Wulandari; Dwi Indra Aprilliandari; Agci Hikmawati (The Indonesian Institute of Science and Technology Research, 2022)
Diphthongs study the sound of language from process to change. This research covers